Remittances and children's capabilities: New evidence from Kyrgyzstan, 2005 - 2008 - Antje Kroeger; Kathryn H. Anderson (Institute for the Study of Labor (IZA), 2012)
The Kyrgyz Republic is one of the largest recipients of international remittances in the world; from a Balance of Payments measure of remittances, it ranked tenth in the world in 2008 in the ratio of remittances to GDP, a rapid increase from 30th place in 2004. Remittances can be used to maintain the household's standard of living by providing income to families with unemployed and underemployed adult members. Remittances can also be used to promote investment not only in businesses and communities but also in people. In this paper, we examine the role that remittances have played in the Kyrgyz Republic in promoting investments in children. Based on the capabilities approach to well-being initiated by Sen (2010), we look at the impact of remittances and domestic transfer payments primarily from internal migration on children's education and health. Our outcomes include enrollment in school and preschool, expenditures, stunting and wasting of preschool children, and health habits of older children. We use unique panel data from the Kyrgyz Republic for 2005-2008 and thus control for some of the biases inherent in cross-sectional studies of remittances and family outcomes. We find that overall remittances and domestic transfers have not promoted investments in the human capital of children. Specifically, preschool enrollments were higher in the urban north but secondary school enrollments were lower in other regions in remittance receiving households; expenditures were also negatively affected in the south and the mountain areas. These negative enrollment results were larger for girls than for boys. We also found evidence of stunting and wasting among young children and worse health habits among boys in remittance or transfer receiving households. In the long run, Kyrgyzstan needs human capital development for growth; our results suggest that remittances are not providing the boost needed in human capital to promote development in the future.
urn:nbn:de:101:1-201203145660
Keywords: C23; F22; I21; O53; R23; 330; children's education and health; remittances; Central Asia; Rücküberweisung (Migranten); Kinder; Bildungsinvestition; Gesundheit; Schulbesuch; Capability Approach; Kirgisistan